Stereoelectronic manipulation of ligands for perovskite solar cells - Tinghuan Yang; Erxin Zhao; Nan Wu; Xiaoming Chang; Chenqing Tian; Hai-Long Wang; Lu Zhang; Nannan Gu; Ting Nie; Ye Yang; Zheng Zhang; Tianfei Xu; et al. (Nature, 2026)
Abstract Interfacial losses at perovskite/charge transport layer (CTL) heterojunctions persist as a critical barrier to achieving high-performance perovskite solar cells (PSCs) 1–5 . Although molecular ligands can passivate interfacial vacancy defects, their vertical anchoring geometry compromises charge transport by increasing interfacial transport pathways. Here we demonstrate that stereoelectronic manipulation of ligand adsorption topology advances interfacial minimum energy loss for efficient and stable PSCs. By strategically replacing benzene carbons with nitrogen atoms to create pyridine or pyrimidine rings, we design ligands that concurrently anchor to the perovskite through Pb–N coordination bonds and Pb–I–π interactions, endowing a single molecule with dual, synergistic binding modes. This mutually reinforcing stereoelectronic interplay drives thermodynamically favourable planar alignment of ligands, enabling atomic-scale defect mitigation while maintaining sub-nanometre-scale charge transfer across the interface. The optimized interfacial architecture achieves a stabilized power output of 26.85%, with certificated reverse-scan and forward-scan efficiencies of 27.41% and 26.35%, respectively. Furthermore, the solar modules exhibit exceptional operational stability, retaining 85.8% of initial module efficiency after 258 days of outdoor real-time field testing.